Improving Students’ Reading Comprehension Skills through the GOSCIENCE Project’s Methods - Cintia COLIBABA; Anca COLIBABA; Irina GHEORGHIU; Anais COLIBABA; Ovidiu URSA (Bulletin of University of Agricultural Sciences and Veterinary Medicine Cluj-Napoca: Horticulture, 2019)
The article is based on the GoScience project funded by the Erasmus+ programme. The project relies on the European context, where in spite of the development of science and technology fewer and fewer students follow a science career let alone one in agricultural sciences. As a result professors of science and their students from seven European countries have joined their efforts to identify innovative practices to motivate students to study and pursue a career in science. The aim of the project is to develop innovative tools for science teaching and learning which will make science education more appealing and empower students to take ownership of their learning. The article studies the main findings of the project’s research on methods and techniques used in teaching science and reading comprehension skills applied to scientific texts in foreign languages in Romania. The project’s research has identified a common conclusion: an effective reading comprehension instruction would bring about significant changes in students’ motivation to study science.